"Holy anorexia"—relevant or relic? Religiosity and anorexia nervosa among Finnish women. Issue 4 (27th March 2017) - Sipilä, Pyry; Harrasova, Gulnara; Mustelin, Linda; Rose, Richard J.; Kaprio, Jaakko; Keski‐Rahkonen, Anna
Abstract: Since medieval times, an association between religiosity and anorexia nervosa has been suggested, but few systematic studies exist. This study examines in a nationwide setting whether personal or family religiosity is associated with lifetime anorexia nervosa among women in adolescence and early adulthood. Women ( N = 2, 825) from the 1975 to 1979 birth cohorts of Finnish twins were screened for lifetime DSM‐5 anorexia nervosa ( N = 92). Parental religiosity was assessed by self‐report when the women were aged 16 years. The women self‐reported their religiosity at ages 16 and 22 to 27 years. Parental religiosity did not increase the risk of lifetime anorexia nervosa, and neither did religiosity of the women themselves in adolescence. In early adulthood, a J‐shaped curve was compatible with the data, indicating increased risk both at low and high levels of religiosity, but this result was statistically non‐significant. Religiosity was weakly negatively correlated with body dissatisfaction. There was some suggestive evidence for socioregional variation in the association of religiosity with lifetime anorexia nervosa. In this first population study to directly address religiosity and anorexia nervosa, no evidence was found for a significant association of religiosity with anorexia nervosa either at the personal or family level. Some regional differences are possible. A modest protective association of religiosity with body dissatisfaction is also possible. Despite compelling case descriptions of "holy anorexia, " religiosity does not appear to be a central factor in the development of anorexia nervosa in Finland, a highly secularized Christian country.